Interactive Effects of Team Virtuality and Work Design on Team Functioning - Handke, L.; Klonek, Florian; Parker, Sharon; Kauffeld, S. (SAGE PUBLICATIONS INC, 2019)
© The Author(s) 2019. This review study aimed to investigate how team work design shapes the impact of team virtuality on team functioning. Based on 48 studies, we identified key work design variables that influence both team functioning, that is, team performance and intermediary outcomes (i.e., team processes and emergent states), under conditions of high virtuality (or in interaction with virtuality). First, while outcome interdependence showed positive effects on the functioning of virtual teams, particularly via motivational increases, task interdependence showed mixed results. Second, high levels of knowledge characteristics (e.g., task complexity) appear to worsen team functioning within virtual contexts, likely because these characteristics add to the demands of an already demanding context. Third, job resources (e.g., feedback) showed positive associations with team functioning, suggesting these variables might buffer the high demands of virtual work. Given these results, more investigations that explicitly examine the interaction between work design and team virtuality are needed.